Almost half of children and adolescents had unmet need 6 months after their traumatic brain injury. (8th February 2023) - Dahl, Hilde Margrete; Holthe, Ingvil Laberg; Løvstad, Marianne; Tverdal, Cathrine; Andelic, Nada; Myhre, Mia C.
Abstract: Aim: Very few studies have focused on how children with traumatic brain injuries (TBI) access and use publicly funded healthcare and educational services. We aimed to compare the symptoms, recovery and service use of children with TBIs and a control group with other traumatic injuries. Methods: This case–control study was conducted at Oslo University Hospital, Norway, from 2015 to 2020. It focused on 49 patients aged 1–15 years who were hospitalised with TBIs and compared them with 51 matched patients with other traumatic injuries. Unmet needs were based on reports from parents, patients and clinicians 6 months after the injury. Results: Many children hospitalised after TBIs experienced persistent cognitive and emotional symptoms that effected their return to school and subsequent social interactions. These were associated with reduced quality of life. Nearly half (47%) of the children in the TBI group had unmet needs after 6 months, compared to 12% of the controls. Patients with TBIs also had more symptoms and showed less favourable recoveries than the controls. Conclusion: Paediatric patients with TBIs had long‐term cognitive and emotional symptoms that affected their return to school and social functioning. Almost half of them had unmet needs 6 months after their acute injury.